Morphoanatomical and Biochemical Changes in the Roots of Rice Plants Induced by Plant Growth-Promoting Microorganisms - Rêgo, Marcela Cristiane Ferreira; Ilkiu-Borges, Fernanda; Filippi, Marta Cristina Corsi de; Gonçalves, Letícia Almeida; Silva, Gisele Barata da (Journal of Botany, 2014)
The goal of the present study was to characterize anatomical and biochemical changes in rice plant roots in response to seed treatment with rhizobacteria (Burkholderia pyrrocinia (R-46) + Pseudomonas fluorescens (R-55)) and Trichoderma asperellum (Ta: mixture of strains T-06, T-09, T-12, and T-52). The experimental design was completely randomized, with six treatments (R-46, R-55, R-46 + R-55, Ta+ R-46 + R-55, Ta, and control) and ten replicates. Treatments Ta and R-46 + R-55 increased the root length and diameter as well as the cortex expansion and induced a 2% expansion of the aerenchymal space. Treatments Ta and R-46 increased the vascular cylinder diameter. The number of protoxylem poles and metaxylem vessel elements was increased by R-46 and R-55. The total phenol content increased with treatments Ta, R-46 + R-55, R-46, and R-55, and all the treatments increased the flavonoid content. The lignin content increased with the Ta and R-55 treatments. All the root architecture modifications resulting from the interaction between seedlings and bioagents (rhizobacteria and Trichoderma spp.) observed in the present study favored the root plasticity of rice seedlings.